DESIGN OF HAZARDOUS WASTE STATION IN XYZ RADIOACTIVE INDUSTRY - Stacia Dea Prameswari; Muhammad Aang Nurhadi; Irfan Rizaldi; Mutiara Octaviani; I Wayan Koko Suryawan; Betanti Ridhosari (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
A hazardous waste station must be designed following Regulation of the Minister of Environment and Forestry Number P.12 of 2020 concerning the Storage of Hazardous Waste so as not to cause environmental impacts. The purpose of this design is to improve the design criteria for the hazardous waste station in accordance with applicable regulations. The type and volume of hazardous waste storage have jerry can shape in 60 and 30-liter volumes, HDPE drum, and pallet. Each container is equipped with a symbol and label. Hazardous liquid waste and hazardous solid waste are designed with the dimensions of 10.66m x 8.2m and 8.65m x 8.2m. Each is equipped with coordinate, spill kit, fire extinguisher, pallet, shower & eyewash, and container. The new design of hazardous waste selected has met the requirements in the regulation, safe from outside interference and environmental impacts.